2014
DOI: 10.1016/j.artint.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The price of query rewriting in ontology-based data access

Abstract: We give a solution to the succinctness problem for the size of first-order rewritings of conjunctive queries in ontologybased data access with ontology languages such as OWL 2 QL, linear Datalog ± and sticky Datalog ± . We show that positive existential and nonrecursive datalog rewritings, which do not use extra non-logical symbols (except for intensional predicates in the case of datalog rewritings), suffer an exponential blowup in the worst case, while first-order rewritings can grow superpolynomially unless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 39 publications
1
57
0
Order By: Relevance
“…The only previously known result in Fig. 2a is indicated by the white dotted line; for details, see [34,54].…”
Section: Our Contributionmentioning
confidence: 99%
See 3 more Smart Citations
“…The only previously known result in Fig. 2a is indicated by the white dotted line; for details, see [34,54].…”
Section: Our Contributionmentioning
confidence: 99%
“…Kikot et al [57] and Thomazo [84] identified common structures in UCQ-rewritings and compactified them into unions of semiconjunctive queries (USCQs)-positive-existential (PE) formulas with matrices of the form ∨∧∨-of size |T | · 2 O ( |q | 2 ) . The first lower bounds on the size of FO-, PE-and NDL-rewritings 4 were obtained 1:4 M. Bienvenu, S. Kikot, R. Kontchakov, V. V. Podolskii, and M. Zakharyaschev by Gottlob et al [34] who constructed a sequence of OMQs (with tree-shaped CQs) whose PEand NDL-rewritings can only be of exponential size, while FO-rewritings are superpolynomial unless NP ⊆ P/poly.…”
Section: Problems: Succinctness and Complexitymentioning
confidence: 99%
See 2 more Smart Citations
“…It is to be noted that there exist CQs q and QL TBoxes T any PE-rewritings of which are of exponential size in |q| provided that the rewritings use the same symbols as in q and T (Kikot et al, 2012a). One can always reduce the size of PE-rewritings to polynomial by employing two new constants that do not occur in q; for details and further references, consult (Gottlob et al, 2014).…”
Section: Tree-witness Pe-rewriting For Full Qlmentioning
confidence: 99%